Improving Critical Thinking Skills In Mathematics Content Using The Sisi Ceria Model In Grade Iv Elementary School Students - Aulia, Maya; Cinantya, Celia (Berpusi Publishing, 2023)
The problems that occur are low activity, critical thinking skills and student learning outcomes which are caused by several things, namely one-way learning, the learning atmosphere is less enjoyable, students are less actively involved in solving problems and learning is less meaningful. The aim of this research is to describe teacher activities and analyze activities, critical thinking skills and student learning outcomes in the mathematical content of plane figures in class IV. This type of research is classroom action research (PTK). The research subjects were fourth grade students at SDN Kolam Makmur, Barito Kuala Regency. The results of this research are the application of the SISI CERIA model, teacher activity meets the very good criteria, student activity reaches the criteria, all students are active